2014
DOI: 10.1603/en13227
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Effects of Emerald Ash Borer-Induced Ash Mortality and Canopy Gap Formation on Epigaeic Beetles

Abstract: Exotic herbivorous insects have drastically and irreversibly altered forest structure and composition of North American forests. For example, emerald ash borer (Agrilus planipennis Fairmaire) from Asia has caused wide-scale mortality of ash trees (Fraxinus spp.) in eastern United States and Canada. We studied the effects of forest changes resulting from emerald ash borer invasion on epigaeic or ground beetles (Coleoptera: Carabidae) along a gradient of ash dieback and gap sizes in southeastern Michigan. Ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 47 publications
3
38
2
Order By: Relevance
“…One of the only published studies on the impacts of EAB on wildlife focused on the indirect effects of EAB-induced mortality to ground beetle community assemblages (Coleoptera: Carabidae) in infected ash stands in Michigan [37]. The results of this study indicated that species diversity decreased in ash stands in response to tree mortality and increasing canopy gap size [37].…”
Section: Animal Responses In Post-eab Black Ash Wetlandsmentioning
confidence: 72%
See 1 more Smart Citation
“…One of the only published studies on the impacts of EAB on wildlife focused on the indirect effects of EAB-induced mortality to ground beetle community assemblages (Coleoptera: Carabidae) in infected ash stands in Michigan [37]. The results of this study indicated that species diversity decreased in ash stands in response to tree mortality and increasing canopy gap size [37].…”
Section: Animal Responses In Post-eab Black Ash Wetlandsmentioning
confidence: 72%
“…The results of this study indicated that species diversity decreased in ash stands in response to tree mortality and increasing canopy gap size [37]. Hydric black ash wetlands had the most unique assemblage of ground beetles, with numerous beetle species only found in the hydric moisture category, but also had moderate turnover (25%) of species from 2006-2007 [37].…”
Section: Animal Responses In Post-eab Black Ash Wetlandsmentioning
confidence: 78%
“…The speed, synchrony, and specificity of ash mortality differs from gap-phase dynamics caused by other forest insects. EAB-induced ash mortality increases both the frequency of canopy gaps as ash trees die ( Figure 1A) and the accumulation of ash CWD as trees fall ( Figure 1B) [78,89]. Our model predicts that this pattern of tree mortality has an inverse temporal relationship in the effect sizes of canopy gaps and accumulation of ash CWD on ground-dwelling invertebrate communities (Table 1), as the effects of canopy gaps diminish with canopy closure, while the effects of ash CWD are predicted to increase and change over time as trees fall and decompose [60].…”
Section: Invasive Insectsmentioning
confidence: 99%
“…During early stages of ash mortality, decreased invertebrate richness and diversity was reported in canopy gaps, owing to the decreased activity-abundances of harvestmen, scarab beetles, camel crickets, and springtails [60]. Activity-abundance of ground beetles initially was lower in canopy gaps, but these effects were ephemeral, suggesting some degree of resilience to small-scale canopy gaps [53,89]. During late stages of ash mortality, higher densities of ground-dwelling invertebrates were observed near ash CWD, including earthworms, spiders, harvestmen, isopods, millipedes, beetles, and springtails [78].…”
Section: Invasive Insectsmentioning
confidence: 99%
See 1 more Smart Citation